2021
DOI: 10.1055/s-0041-1731692
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus Management: The Utilization of a Hybrid Telehealth and In-Person Delivery Model

Abstract: Telehealth, or the delivery of healthcare services from a distance, has historically been used to provide care to underserved populations and to those unable to visit a healthcare center. During the ongoing global COVID-19 pandemic, some providers of tinnitus healthcare services incorporated telehealth into their clinical protocols to allow for continued care for their patients while adhering to social distancing guidelines and safety measures. Bothersome tinnitus can negatively impact one's quality of life. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…In one case study, a hybrid delivery model (in-person for audiological assessment, coupled with telehealth for counseling and education) showed promise to both the patient and provider to the extent that it supported continuity of care during the COVID-19 pandemic. 22 In another study on the use of a virtual platform for tinnitus management for providers, speech therapists indicated a high degree of acceptance, 23 which is an important contextual factor for the implementation of innovative practices in healthcare. 24 Finally, high acceptance of telehealth was reported in a study of patients with bothersome tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…In one case study, a hybrid delivery model (in-person for audiological assessment, coupled with telehealth for counseling and education) showed promise to both the patient and provider to the extent that it supported continuity of care during the COVID-19 pandemic. 22 In another study on the use of a virtual platform for tinnitus management for providers, speech therapists indicated a high degree of acceptance, 23 which is an important contextual factor for the implementation of innovative practices in healthcare. 24 Finally, high acceptance of telehealth was reported in a study of patients with bothersome tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…This can be primarily explained by the fact that many of these cases had been previously evaluated by an outside otolaryngology clinic and subsequently referred after examination. Notwithstanding, several innovations have been studied to address this issue, including the use of store-andforward otoscopes for referring physicians to send otoscope images to specialist or hybrid virtual visits with telehealth facilitators, including primary care providers and audiologists, using otoscopes live with a virtual otolaryngologist (3)(4)(5)8,9,(30)(31)(32)(33). In cases of cerumen impaction, it may be feasible in some cases to have the patient present to a local facility for cerumen removal to facilitate visualization of the tympanic membrane if deemed important for care (12) Recognizing certain potential limitations, current home digital video otoscope systems and home self-administered audiograms may be potential future options in select cases (34).…”
Section: Visit Indications Less Amenable To Virtualmentioning
confidence: 99%
“…To address the burden of in-person care of patients with tinnitus, self-management, self-help, and low-contact treatment forms are on the rise. Partially owing to the COVID-19 pandemic, telerehabilitation, that is, delivery of care from a distance, became a necessity rather than an opportunity [28][29][30]. Studies have shown that low-contact treatment provided from a distance through applications and videoconferencing can be used as a substitution of or an addition to in-person clinical care for several conditions [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Telerehabilitation is remotely delivering care with any form of technology; this can indeed be by using audio or video communication but also by making use of messaging platforms for guidance, software in smartphone apps with rehabilitative purposes, virtual reality, or a combination of all these forms of technology [38,39]. In the field of audiology and, more specifically, in the field of tinnitus, telerehabilitation in both full and hybrid forms has the potential to be very useful during the entire therapeutic process [29,40,41]. Telerehabilitation has been used as an aid for early screening, initial evaluation, diagnosis, therapy, long-term monitoring, provision of web-based support, etc [40].…”
Section: Introductionmentioning
confidence: 99%